2023
DOI: 10.1126/sciadv.add0960
|View full text |Cite
|
Sign up to set email alerts
|

TEAD4 is a master regulator of high-risk nasopharyngeal carcinoma

Abstract: The molecular basis underlying nasopharyngeal carcinoma (NPC) remains unclear. Recent progress in transcriptional regulatory network analysis helps identify the master regulator (MR) proteins that transcriptionally define malignant tumor phenotypes. Here, we investigated transcription factor-target interactions and identified TEA domain transcription factor 4 (TEAD4) as an MR of high-risk NPC. Precisely, TEAD4 promoted NPC migration, invasion and cisplatin resistance, depending on its autopalmitoylation. Mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…Liu et al 18 suggested that TEAD4 plays a significant role in tumor progression and metastasis in colorectal cancer, independently of YAP. Transcriptional activity of TEAD4, independent of YAP or transcriptional coactivator with PDZ-binding motif, was also observed in nasopharyngeal cancers 38 . In this study, YAP1-low/TEAD4-high expression was significantly associated with aggressive clinicopathologic variables in CCRCC.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Liu et al 18 suggested that TEAD4 plays a significant role in tumor progression and metastasis in colorectal cancer, independently of YAP. Transcriptional activity of TEAD4, independent of YAP or transcriptional coactivator with PDZ-binding motif, was also observed in nasopharyngeal cancers 38 . In this study, YAP1-low/TEAD4-high expression was significantly associated with aggressive clinicopathologic variables in CCRCC.…”
Section: Discussionsupporting
confidence: 52%
“…Transcriptional activity of TEAD4, independent of YAP or transcriptional coactivator with PDZ-binding motif, was also observed in nasopharyngeal cancers. 38 In this study, YAP1-low/ TEAD4-high expression was significantly associated with aggressive clinicopathologic variables in CCRCC. Regardless of the YAP1 expression status, CCRCC with high TEAD4 expression was associated with worse OS and DFS, implying that high TEAD4 expression plays a critical role in determining survival.…”
Section: Discussionmentioning
confidence: 53%
“…Additionally, some studies have demonstrated that VP is proteotoxic and lacks specificity, 160 which limits its application in the clinic. Nevertheless, inhibitors of YAP–TEAD/TEAD, including MYF‐01‐37, 161 VGLL4 peptide mimics, 23 peptide 17, 162 and MGH‐CP1, are still being explored 163 . Unlike others in the group, MYF‐01‐37 has since been identified as a covalent binding agent for TEAD, which effectively targets NSCLC cells with EGFR mutations 161 .…”
Section: Targeting Therapy Of Hippo Signalingmentioning
confidence: 99%
“…Regarding the mechanism, VGLL4 peptide mimetics compete with YAP binding to TEAD via the TDU domain, thus functioning as a YAP antagonist 23 . The MGH‐CP1, an inhibitor of auto‐palmitoylation of TEAD2 and TEAD4, inhibits nasopharyngeal carcinoma cell migration, invasion, and cisplatin resistance 163 . In addition, work by Pobbati et al 164 .…”
Section: Targeting Therapy Of Hippo Signalingmentioning
confidence: 99%
See 1 more Smart Citation